Financial Distress, Environmental Performance, and Carbon Emission Disclosure - Muhammad Faisal; Farris Althaf Pratama (EQUITY, 2024)
This research aims to obtain empirical evidence related to the effect of financial distress and environmental performance on carbon emission disclosure. The research methodology used is quantitative and used secondary data from non-financial companies listed on the Indonesia Stock Exchange (IDX). The sampling technique in this research is purposive sampling, with a total of  33 companies sampled over the period from 2017 to 2021. The analysis method used is multiple linear regression analysis, conducted using the STATA 17.0 application. The results of this research indicate that financial distress has a negative effect on carbon emission disclosure, whereas environmental performance does not have effect on carbon emission disclosure. Keywords: Carbon Emission Disclosure, Financial Distress, Environmental Perfomance